Introduction to digital professional mobile radio - Ketterling, Hans-Peter A. (Artech House mobile communications library., 2004)
If you are involved in the planning, design, testing, installation, maintenance, sales, or frequency management of digital PMR equipment and systems, this first-of-its-kind book is a smart choice. Written by one of the key developers of PMR, this essential reference provides comprehensive coverage of digital PMR systems, including the standards APCO 25, TETRA and DIIS and the proprietary systems ASTRO, EDACS, iDEN, MOBITEX II and TETRAPOL. Offering unique insight from the author's years of experience working with this technology, the book helps you gain a solid understanding of the transition from analogue to digital PMR. It provides you with methods for estimation coverage distance and bandwidth for digital PMR systems.